PENGARUH CAREER MANAGEMENT TERHADAP TURNOVER INTENTION DENGAN CAREER SATISFACTION SEBAGAI VARIABEL MEDIASI - Yogatama, Gandi Aswaja; Novianti, Fadlilah Karunia (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to examine the effect of career management on turnover intention through career satisfaction as a mediating variable. Design/methodology/approach- The design of this study uses a quantitative approach. The subject of this research is one of the branch offices of the National Bank Company domiciled in East Java Province. Data obtained using a questionnaire. The sampling technique used is total sampling (a sample that represents the population) as many as 35 employees. Findings- Based on an analysis using SEM (PLS), the results show that career satisfaction is able to fully mediate the relationship between career management and turnover intention. Implication- Turnover intention can be minimized through increased satisfaction at a given career path. In addition, the company's efforts are through long-term career management planning so that employees can predict their career in the company in the future. Keywords: Turnover intention, career management, career satisfaction.